(untitled) (Physical Education, Health and Social Sciences, 2025)
Background and Study Aim: Executive-function (EF) challenges—including working memory lapses, weak inhibitory control, and reduced cognitive flexibility—are increasingly visible in mainstream classrooms and often shape academic and behavioral outcomes (Best et al., 2022; Elliott & Gruber, 2023). Teachers serve as the primary gatekeepers for early identification and referral, yet little empirical work examines how their EF knowledge translates into perceptions of student difficulties and referral behavior. This study aimed to investigate (a) teachers’ EF knowledge, (b) their perceptions of EF-related student challenges, and (c) the predictive pathways linking these perceptions to referral patterns within inclusive educational settings. Material and Methods: A cross-sectional, non-experimental survey was administered to 348 mainstream teachers across 42 public-sector schools. Instruments included the Teacher EF Knowledge Scale (Peng et al., 2022), the EF Challenge Perception Scale (Gruber et al., 2023), and the Referral Likelihood Index (Wolff et al., 2022). Descriptive statistics, Pearson correlations, confirmatory factor analysis (CFA), and structural equation modeling (SEM) with maximum-likelihood estimation were conducted. Reliability was evaluated via Cronbach’s alpha, and model fit using CFI, TLI, and RMSEA. Results: Teachers demonstrated moderate EF knowledge and moderate–high perception of EF challenges. EF knowledge strongly predicted perceived challenge severity (β = .42, p < .001), which predicted referral likelihood (β = .51, p < .001). Model fit indices were acceptable (CFI = .954; RMSEA = .049). Experienced teachers showed lower referral propensity than novice teachers. Conclusion: Teachers’ perceptions significantly mediate the link between EF knowledge and referral decisions. Strengthening EF literacy may improve early identification and reduce inconsistent referral practices, supporting inclusive education policy aims.